Project Primate (Institutional Knowledge at Singapore Management University, 2001)
President Janice Bellace (with flowers), students and faculty at Zouk Club on 13 June 2001. A group of Singapore Management University undergraduates organised SMU’s first student-run service project, Project Primate. As part of the community service module in their leadership and team building course, they adopted a baby Sumatran orang utan and raised funds for wildlife conservation. The fund-raising efforts culminated in a bash at Zouk.